Experimental research on the formation of cognitive healthcare qualities of future engineers-technologists of the food industry - Lazarieva Т.; Blahyi , O. (Problems of Engineer-Pedagogical Education, 2020)
Modernization of vocational training of future food technology engineers requires the development of professionally important healthcare qualities. Thus, future specialists should not only carry out technological activities in manufacturing healthcare products, but also implement medical and physiological knowledge on the structure and functioning of the body of consumers and biological knowledge of the health properties of biologically active substances and nutritional supplements. This intensifies the need for future engineerstechnologists of the food industry to have cognitive qualities that ensure their professional readiness for the development and implementation of the healthcare function of food products. The present research aimed to experimentally study the level of the development of cognitive healthcare qualities of future engineerstechnologists of the food industry in the process of their professional training. The experimental pedagogical study on the development of cognitive healthcare qualities of future engineers-technologists of the food industry was conducted in 2015-2018 and went through three stages, which were ascertaining, formative and comparative. The results of the study made it possible to generalize the structure of cognitive healthcare qualities of future professionals, namely their ability to think systematically, ability to imagine and represent the states, phenomena and processes of medical-physiological, biological and technological components, mnemonic ability to memorize large amounts of information on medical, physiological, biological and technological components, ability to concentrate attention in the process of creating healthcare products, ability to perceive and understand phenomena, processes, raw materials and products. The results of the conducted pedagogical experiment confirm the increase in the level of the development of cognitive healthcare qualities of future food technology engineers, providing the authors’ methodology is developed and implemented, which is based on ensuring the unity of competent, systematic, activity-based and problem-solving approaches to vocational training of specialists in the relevant field and the integration of medical-physiological, biological and technological components of the content of their studies.